In vitro study of the cytotoxic and genotoxic effects of indomethacin-loaded Eudragit (R) L 100 nanocapsules - Froder, J. G. [UNESP]; Dupeyron, D.; Carvalho, J. C. T.; Maistro, E. L. [UNESP] (Funpec-editora, 2016)
Indomethacin is a non-steroidal anti-inflammatory agent included in one of the most commonly used drug classes worldwide. The use of this drug results in certain side effects, including gastrointestinal complications. Therefore, there exists a need to develop better methods for the delivery of such drugs into the body, such as those employing nanoparticles. The aim of the present study was to evaluate the cytotoxic and genotoxic effects of indomethacin-loaded Eudragit (R) L 100 nanocapsules (NI; based on methacrylic acid and methyl methacrylate) on cells unable (lymphocytes) and able to metabolize drugs (HepG2 cells), using comet and cytokinesis-block micronucleus (CBMN) assays in vitro. Cells were exposed to NI at concentrations of 5, 10, 50, 125, 250, and 500 mu g/mL. The comet assay showed that NI induced no significant DNA damage in either cell type at any of the concentrations tested. The CBMN test confirmed these results; however, the highest concentration of 500 mu g/mL resulted in a small but statistically significant clastogenic/aneugenic effect in HepG2 cells. These findings should encourage the development of new investigations of this nanomaterial as a delivery vehicle for anti-inflammatory drugs, such as indomethacin.
Keywords: Comet assay; Micronucleus test; Eudragit L 100; MTT assay; Drug delivery